Managing Dismounted Complex Blast Injuries in Military & Civilian Settings Guidelines and Principles (Springer International Publishing, 2018)
This text is designed to present a comprehensive and state-of the-art approach to dismounted complex blast injuries. Sections address care of these patients from the point of injury through rehabilitation. The specific areas addressed include blast mechanics, stabilization and hemorrhage control at the point of injury, early resuscitation at local hospitals, a systematic approach to surgical care, and finally reconstruction and rehabilitation. Specific chapters focus on operative management of pelvic, abdominal, genitourinary, orthopedic, neurological and thoracic injuries. The authors of each chapter, are experts in treating DCBIs that have had direct hands-on experience through military deployments in Iraq and Afghanistan. Each chapter describes patient presentation and an algorithm outlining treatment with support from the literature. The text will conclude with three chapters. The first explores new advances in care that can be applied to these injuries. The second highlights the organization and team approach to care of these patients. Finally, the last chapter describes an actual case, cared for by the editors, that encompasses points from the chapters in the text. Extensive illustrations and flow diagrams are used throughout the text. This text is specifically designed to be a "how to" guide for inexperienced military and civilian providers. The chapters are organized in a step-wise fashion that mirrors the patient's course from point of injury through their hospital course. Combining authors' experience with illustrations and algorithm diagrams creates a text that is easy to use as a reference text or basis of training for future military and civilian surgeons.